PENGARUH LOAN TO DEPOSIT RATIO (LDR), CAPITAL ADEQUACY RATIO (CAR) DAN RASIO BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSETS (ROA) PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahyuni, Sri Fitri (JURNAL AGRICA, 2016)
Industry financial sectors such as banking, the bank's financial ratios may also improve performance to remain in the public trust. The aimed of this study was to determine the effect of the Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) and the Operating Expenses Operating Income Ratio (ROA) on Return On Assets (ROA) in the banking system. The data used is the financial statements of Conventional Commercial Bank has total assets of over 25 billion in 2008 to 2014. The data analysis technique used is multiple linear regression. The results showed that the variables of the Loan to Deposit Ratio (LDR) and the Capital Adequacy Ratio (CAR) had no significant effect on Return On Assets (ROA). While the Operating Expense Ratio Operating Income (ROA) negative effect on Return On Assets (ROA)Kata Kunci : ROA, LDR, CAR, BOPO